Molecular insights into atypical modes of β-arrestin interaction with seven transmembrane receptors - Maharana, Jagannath (Science, 2024)
β-arrestins (βarrs) are multifunctional proteins involved in signaling and regulation of seven transmembrane receptors (7TMRs), and their interaction is driven primarily by agonist-induced receptor activation and phosphorylation. Here, we present seven cryo–electron microscopy structures of βarrs either in the basal state, activated by the muscarinic receptor subtype 2 (M2R) through its third intracellular loop, or activated by the βarr-biased decoy D6 receptor (D6R). Combined with biochemical, cellular, and biophysical experiments, these structural snapshots allow the visualization of atypical engagement of βarrs with 7TMRs and also reveal a structural transition in the carboxyl terminus of βarr2 from a β strand to an α helix upon activation by D6R. Our study provides previously unanticipated molecular insights into the structural and functional diversity encoded in 7TMR-βarr complexes with direct implications for exploring novel therapeutic avenues.